2022
DOI: 10.1002/oby.23369
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and breast cancer: Preventive and therapeutic possibilities for bariatric surgery

Abstract: Breast cancer is the most common and second deadliest malignancy in women. With rising obesity rates and building evidence for a strong association with obesity, the incidence of breast cancer can be expected to increase. Weight loss reduces breast cancer risk, the mechanisms of which are still poorly understood. As an effective therapy for obesity, bariatric surgery may be a powerful tool in breast cancer prevention and treatment. This review details the potential physiologic mechanisms that may underlie this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…When compared to conventional treatment, BMS results in more substantial and durable weight loss while improving inflammatory markers, insulin sensitivity (HOMA-IR) and resolving other underlying disease processes, including metabolic syndrome, T2DM, glycosylated haemoglobin (HbA1c), NASH, aromatase activity, visceral obesity, hypoxia and OSA [ 23 , 31 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. RYGB surgery has been shown to decrease macrophage infiltration and crown-like structures (CLS) in subcutaneous adipose tissue (SAT), indicating improvement in local white adipose tissue (WAT) inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to conventional treatment, BMS results in more substantial and durable weight loss while improving inflammatory markers, insulin sensitivity (HOMA-IR) and resolving other underlying disease processes, including metabolic syndrome, T2DM, glycosylated haemoglobin (HbA1c), NASH, aromatase activity, visceral obesity, hypoxia and OSA [ 23 , 31 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. RYGB surgery has been shown to decrease macrophage infiltration and crown-like structures (CLS) in subcutaneous adipose tissue (SAT), indicating improvement in local white adipose tissue (WAT) inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in leptin, cytokines, PGE2 and NF-κB activation and the resultant lowering of WAT aromatase activity after bariatric surgery are associated with larger postoperative falls in the serum oestradiol at 12 months after surgery in older women (53.9 to 35.7 pg/mL) as compared to oestradiol in younger women (94.85 to 73.62 pg/mL). Changes in oestrogen and testosterone metabolism and the LH, FSH and SHBG levels after bariatric surgery result in the improvement of polycystic ovary syndrome (96% resolution) and fertility in premenopausal women, a potential decrease in future oestrogen-sensitive cancers in women and hypogonadism (87% resolution) in males [ 72 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery remains the most effective treatment for severe obesity, demonstrating long‐term weight loss [4], remitting chronic metabolic diseases [29], reducing cardiovascular‐related disorders [30], and decreasing incidence of obesity‐related cancers [9]. Furthermore, findings of reduced cancer incidence following bariatric surgery has launched mechanistic discovery underlying the benefits of bariatric surgery, including reductions in tumor initiation and progression, cellular inflammation, insulin resistance, steatosis, lipid peroxidation, and oxidative stress—all pathways of etiological relevance for cancer [4,8,10,31‐34]. Although our study did not explore mechanistic aspects of bariatric surgery with reduced cancer incidence, this study clearly identified sex‐related differences for reduced cancer incidence; when cancer risk was stratified by sex, only female surgery patients demonstrated significant lowering of cancer incidence compared with nonsurgical females.…”
Section: Discussionmentioning
confidence: 99%
“…69 In women with obesity, conservative and/or surgical management of obesity can reduce cancer risk. 70 Bariatric surgery may decrease the incidence of breast and endometrial cancer. 70 Early mammogram screening can be considered for individuals with obesity and gigantomastia if there is concern or uncertainty on breast examination.…”
Section: Obesity-related Cancersmentioning
confidence: 99%
“…In women with obesity, conservative and/or surgical management of obesity can reduce cancer risk 70 . Bariatric surgery may decrease the incidence of breast and endometrial cancer 70 .…”
Section: Lifelong Health Implications For Women Living With Obesitymentioning
confidence: 99%